CREATING DESCRIPTORS FOR EVALUATING ACADEMIC ACHIEVEMENTS IN COMPUTER SCIENCE - Orazaliyeva А.Е.; Madyarova Г.А.; Moldabekov Б.К.; Yerniyazova С.Н. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
The scientific article analyzes the methods of assessing students’ knowledge in computer science, examines the possibilities of their application in the educational process. Special attention was paid to the specifics of assessing academic performance using tests, projects, essays and other assessment tools and how to choose and use them. The expert examination of scientific works of scientists on the use of assessment tools was carried out, foreign and domestic experience was analyzed. The main factors were the purpose of the lesson, the level of training of students, the time spent, the availability of resources, the advantages and disadvantages of various assessment tools were studied. Based on the results of the analysis, the study analyzed examples of using an assessment tool for a specific task. The main feature of teaching computer science is that students are given many tasks to create a project and write an essay. For teachers, the lack of assigned descriptors for project and essay assessment creates a number of problems. Based on the results of the study, a project was created to create websites and descriptors for evaluating the essay "the role and influence of artificial intelligence in the modern world". In order to increase the effectiveness of computer science lessons, descriptors of an objective assessment of students’ knowledge were substantiated. In the study, descending descriptors were created (a decrease in the point value when evaluating readability). This approach not only contributes to the objective assessment of students’ knowledge, but also reduces subjectivity in the assessment process. The use of decreasing descriptors complements the methodological complex and affects the adaptation of the level of training of students.